Interpersonal adaptation in teacher-student interaction. (June 2018) - Pennings, Helena J.M.; Brekelmans, Mieke; Sadler, Pamela; Claessens, Luce C.A.; van der Want, Anna C.; van Tartwijk, Jan
Abstract: Teacher-student relationships play a crucial role in the quality of teaching and learning. Daily interpersonal interactions in classrooms are the building blocks of teacher-student relationships. With the aim to add to insights on teaching and learning, we specifically explored interpersonal adaptation in daily interactions. Adaptation, i.e., how people respond to each other's actions and reactions, is a defining characteristic of interactions. We studied 35 classrooms in secondary education. Although the degree and nature of interpersonal adaptation was in general consistent with interpersonal theory, degree of adaptation varied considerably between classrooms. In classrooms with a more preferred teacher-student relationship, behaviour of teachers and the adaptation to the behaviour of their students was more in accordance with professional standards, compared to classrooms with a less preferred relationship. Conceptualizations and results of the present study contribute to theory on teacher-student interaction, as well as the practice of teacher professional development (e.g., video coaching). Highlights: Studying micro-processes of adaptation in teacher-student interactions is needed. We obtained continuous time series data using Sadler's computer joystick apparatus. Complementarity, entrainment, and synchronicity of rhythmic qualities were studied. All interactions showed entrainment and synchronicity in cyclical patterns. When necessary, teacher behaviour deviated from the complementarity principle.